Radical reactivity in the condensed phase: Intermolecular versus intramolecular reactions of alkoxy radicals - Carrasquillo, Anthony J. (J Phys Chem Lett, 2015)
Condensed-phase alkoxy (RO) radicals can undergo unimolecular (e.g., intramolecular H-atom abstraction) reactions as well as bimolecular (intermolecular H-atom abstraction) reactions, though the competition between these two channels is not well constrained. Here we examine this branching, by generating RO radicals from the photolysis of a large alkyl nitrite (C(20)H(41)ONO) in hexanes, and nebulizing the mixture into an aerosol mass spectrometer for analysis. Product ions associated with unimolecular (isomerization) reactions were observed to increase upon photolysis. However, no formation of the C(20) alcohol (C(20)H(41)OH, the expected product from RO + RH reactions) was observed, suggesting that bimolecular reactions are at most a minor channel for this condensed-phase system (involving saturated hydrocarbons). This result, combined with previous studies of condensed-phase RO radicals carried out at higher concentrations, suggests that when 1,5-H-atom abstraction reactions are facile (i.e., in which a 1,5-H-atom shift from a secondary or tertiary carbon can occur), this channel will dominate over bimolecular reactions.